Peran Pemerintah dalam Meningkatkan Kesejahteraan Guru Tidak Tetap - Ummi Kulsum (Journal on Education, 2023)
Non-Permanent Teachers are Teachers who are not civil servants but have the same duties. Non-permanent teachers should have the social welfare rights that should be obtained. Teachers deserve a decent wage and social welfare security, but in reality, Non-Permanent Teachers in Cilegon City, their welfare and rights are still neglected. Researchers are interested in examining how the government's role in improving the welfare of teachers is not permanent based on law number 14 of 2005 concerning teachers and lecturers. The methods used in this research are Normative Juridical and Sociological Juridical, with analytical descriptive research types. Collection of research data from skunder data, namely legislation which is the main source of data in research, and primary data as supporting data in the form of interviews with the Head of the Welfare Section and Awards for Energy Development. Analyzed qualitatively normative and Non-Permanent Teachers. The result of the research is the resolution of the problem of non-permanent teacher welfare in Cilegon City that has not been fulfilled, is the authority of the Education Office in implementing the provision of teacher rights which must be in accordance with Article 14 paragraph (1) to obtain income above the minimum living needs and social welfare security. Obstacles in the implementation of teacher welfare due to insufficient APBD. The income that should be received by teachers at least refers to the regional minimum wage of Cilegon City